Udžbenici upravnog prava u Bosni i Hercegovini, Hrvatskoj i Srbiji / Administrative Law Textbooks in Bosnia and Herzegovina, Croatia and Serbia - Ajanović, Enver (Pregled: časopis za društvena pitanja / Periodical for social issues, 2020)
Administrative law textbooks were regularly published in the former Socialist Federal Republic of Yugoslavia. However this literature has some weaknesses. Therefore, readers obtain murky knowledge regarding administrative law. That is the reason behind the necessity of modernizing the way of presenting and explaining administrative law in BiH, Croatia and Serbia. This paper presents basic information on the sociological and normative-dogmatic method for producing the administrative law textbooks for students and other interested readers. Based on methodological objections in the application of methods for the preparation of textbooks of administrative law, the author sketches basic guidelines in order, according to his opinion, such textbooks would be produced in the future.